2009
DOI: 10.1007/s00415-009-5102-x
|View full text |Cite
|
Sign up to set email alerts
|

Orthostatic hypotension associated with an epidermoid tumor of the IV ventricle

Abstract: We report the case of a 32-year-old man with an epidermoid tumor of the fourth ventricle. About 14 years later, he showed a tumor recurrence which was removed. After this procedure the patient complained of presyncopal and syncopal crisis while attempting to stand or walk. On examination, severe orthostatic hypotension was confirmed and autonomic tests were abnormal. The brain MRI showed a tetraventricular hydrocephalus predominating in the fourth ventricle. A ventriculo-peritoneal shunt was performed, and aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 15 publications
1
5
0
2
Order By: Relevance
“…Our present study also revealed cortical thinning in the orbitofrontal, post-central, and inferior temporal cortexes, which are areas known to be associated with the regulation of the autonomic nervous systems, and these findings consistently supported the susceptibility to OH in patients with OH [13,14,15]. Second, some case reports of OH showed an association with structural lesions, such as medullary cavernous angioma or epidermoid tumors of the fourth ventricle [4,5]. The authors of these studies insisted that these structural lesions interrupting the ANS resulted in OH.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Our present study also revealed cortical thinning in the orbitofrontal, post-central, and inferior temporal cortexes, which are areas known to be associated with the regulation of the autonomic nervous systems, and these findings consistently supported the susceptibility to OH in patients with OH [13,14,15]. Second, some case reports of OH showed an association with structural lesions, such as medullary cavernous angioma or epidermoid tumors of the fourth ventricle [4,5]. The authors of these studies insisted that these structural lesions interrupting the ANS resulted in OH.…”
Section: Discussionsupporting
confidence: 60%
“…Several cases have reported that structural abnormalities in the brain may induce OI because specific brain regions modulate the cardiovascular autonomic nervous system (ANS) [4,5]. Moreover, previous studies have demonstrated a volume reduction of the brain in patients with OI [6,7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conforme o tamanho e evolução podem apresentar disfagia e diplopia por envolvimento de nervos cranianos 17 . Gomez et al 12 relataram um caso de CE no IV ventrículo associado a hipotensão ortostática.…”
Section: Relato De Casounclassified
“…Podem ser visíveis septos internos ou pode haver zonas hiperdensas devido ao conteúdo proteico. Ocasionalmente o conteúdo cístico pode ser hiperdenso, simulando uma hemorragia 12 . Após injeção de contraste pode ter um reforço fino na periferia da lesão, provavelmente devido a inflamação perilesional ou transformação maligna 24 .…”
Section: Relato De Casounclassified